Cloning of a Serratia marcescens Gene Encoding Chitinase - Fuchs, R. L. (1986)
Serratia marcescens, a chitinase-producing microorganism, was shown to produce five unique chitinolytic proteins with subunit molecular masses of 21, 36, 48, 52, and 57 kilodaltons. A cosmid library of S. marcescens DNA was constructed in the broad-host-range cosmid pLAFR1 and screened in Escherichia coli for clones capable of degrading chitin. A total of four independent clones (22- to 27-kilobase inserts) were isolated, characterized by restriction endonuclease digestion, and shown to share a common 9.5-kilobase EcoR1 fragment apparently encoding the same 57-kilodalton chitinase, the most abundant chitinase produced by S. marcescens. Chitinase expression from these constructs in both E. coli and Pseudomonas fluorescens 701E1 is apparently driven by an S. marcescens promoter. The significantly higher chitinase levels produced in E. coli relative to those in P. fluorescens 701E1 suggest that E. coli may recognize this promoter sequence more efficiently than P. fluorescens.